Violence among the Youth in Turkey: An Assessment of General Strain Theory - Özbay, Özden (International Journal of Criminology and Sociology, 2016)
Most tests of criminological theories have been carried out in the western world, especially the United States. Agnew developed a General Strain Theory and claimed that it could account for deviance/crime in the developing countries. However, the support for the theory was generally mixed at best. The goal of this study is to examine the major theses of general strain theory in relation to youth violence in Nigde, a small city in central part of Turkey. The data came from a random sample of 974 students drawn from the lists of the university students at Nigde University (N= 12,514). Data were analyzed by using logistic regression analysis. The present study focused on three important research questions: Is the influence of strain on violence positive, Is the impact of strain on violence is mediated by anger, and Is the effect of strain on violence moderated by some criminal and non-criminal copings? The results indicated that few strain variables had direct positive impacts on violence. Anger had positive effect on the dependent variable. Few interactions between the strain and coping variables were observed. In short, the overall results gave a limited support for the three major arguments of general strain theory.